Mark Boyle's journey to the surface of the earth - Locher, J. L. (Edition Hansjörg Mayer, 1978)
"An incredible volume of Mark Boyle's earth art, this book features both color and b & w photography"--Abebooks.com viewed Feb. 19, 2021.